Resin composition and method for manufacturing the same

JP2023163884A5Inactive Publication Date: 2025-02-12IDEMITSU KOSAN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022075090
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-04-28
Publication Date
2025-02-12
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Aromatic polyethers like PEEK face issues of thickening and deterioration during high-temperature molding due to oxidation reactions, leading to decreased processability and mechanical properties of molded articles.

Method used

A resin composition containing aromatic polyether and carbon black in a specific ratio, with carbon black capturing radical components and reducing collisions between aromatic polyether chains to suppress thickening and deterioration.

Benefits of technology

The composition achieves excellent thermal stability and mechanical properties in molded articles by preventing thickening and oxidation, improving processability and mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2023163884000001
    Figure 2023163884000001
  • Figure 2023163884000002
    Figure 2023163884000002
Patent Text Reader

Abstract

To provide: a resin composition including aromatic polyether which is excellent in thermal stability and mechanical characteristics of a molded product; and a method for manufacturing the resin composition.SOLUTION: A resin composition includes aromatic polyether including a structure represented by formulas (1), (2), and (3), and 0.01 pt.mass or more of carbon black with respect to the polyether.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a resin composition and a method for producing a resin composition. Specifically, the present invention relates to a resin composition containing an aromatic polyether that exhibits excellent thermal stability and excellent mechanical properties of molded articles, and to a method for producing the resin composition. [Background technology]

[0002] Aromatic polyethers, such as polyetheretherketone (hereinafter, polyetheretherketone may be referred to as "PEEK"), are known as representative resins of engineering plastics.

[0003] Engineering plastics such as aromatic polyethers are often mixed with various additives before being subjected to molding processes in order to suppress deformation and other problems that occur during heating and melting. Patent Document 1 discloses that a phosphate introduced into a composition containing poly(arylene ether ketone) functions as a stabilizer against thermal oxidation. Patent documents 2 and 3 disclose resin compositions containing aromatic polyether ketones and nanodiamond particles. Patent documents 2 and 3 disclose that the nanodiamond particles function as radical stabilizers when the resin composition is heated. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Special Publication No. 2018-520257 [Patent Document 2] International Publication No. 2017 / 038333 [Patent Document 3] International Publication No. 2018 / 079597 [Overview of the Initiative] [Problems that the invention aims to solve]

[0005] Generally, aromatic polyethers such as PEEK have heat resistance, slidability, chemical resistance, and mechanical properties, and are resins that can replace metals even in harsh environments, especially due to their outstanding heat resistance. However, due to the outstanding heat resistance of aromatic polyethers, during molding, it is necessary to heat them to a high processing temperature corresponding to their melting point. At such high processing temperatures, even if antioxidants such as hindered phenol compounds are mixed, most of them will volatilize or decompose, so thickening of the aromatic polyether used for molding and deterioration due to oxidation reactions or the like may occur.

[0006] Among them, aromatic polyethers synthesized using aromatic chlorine compounds (for example, 4,4'-dichlorobenzophenone) are more likely to have problems of thickening and deterioration during molding under long-term heating conditions and tend to be inferior in thermal stability compared to aromatic polyethers synthesized using aromatic fluorine compounds (for example, 4,4'-difluorobenzophenone). Thickening during melting causes a decrease in the processability when melting an aromatic polyether to produce a molded product. In addition, deterioration due to oxidation reactions or the like during melting causes a decrease in the mechanical properties of the molded product. In conventional technologies including Patent Documents 1 to 3, further room for improvement has been found from the perspective of solving such problems.

[0007] One object of the present invention is to provide a resin composition containing an aromatic polyether and a method for producing the resin composition, which are excellent in thermal stability and excellent in the mechanical properties of the molded product.

Means for Solving the Problems

[0008] As a result of intensive studies, the present inventors have found that a resin composition obtained by mixing an aromatic polyether and carbon black at a predetermined ratio is excellent in thermal stability and excellent in the mechanical properties of the molded product obtained through heat melting, and have completed the present invention. According to the present invention, the following resin compositions and the like can be provided. 1. It includes a structural unit represented by the following formula (1), a structural unit represented by the following formula (2), and a structure represented by the following formula (3), 1 Aromatic polyethers in which the ratio of the peak intensity of the peak originating from the structural unit represented by formula (2) that appears around a chemical shift of 7.34 ppm in 1H-NMR measurements to the peak intensity of the peak originating from the structure represented by formula (3) that appears in the chemical shift range of 7.69 ppm to 7.75 ppm is greater than 0%, A resin composition comprising 0.01 parts by mass or more of carbon black per 100 parts by mass of the aromatic polyether. [ka] 2. The resin composition according to claim 1, wherein the content of carbon black per 100 parts by mass of the aromatic polyether is 10 parts by mass or less. 3. The amount of dibutyl phthalate absorbed by the carbon black is 40-400 cm³. 3 The resin composition according to 1 or 2, wherein the amount is / 100g. 4. The resin composition according to any one of 1 to 3, wherein the pH of the carbon black is 4.0 or higher. 5. The resin composition according to any one of 1 to 4, wherein the average particle size of the carbon black is 5 to 200 nm. 6. The specific surface area of ​​the carbon black is 10 to 250 m². 2 The resin composition described in any of 1 to 5, which is / g. 7. The resin composition according to any one of 1 to 6, wherein the aromatic polyether contains a structural unit represented by the following formula (4). [ka] 8. A process to produce an aromatic polyether by reacting 4,4'-dichlorobenzophenone with hydroquinone, A method for producing a resin composition according to any one of 1 to 7, comprising the step of mixing 0.01 parts by mass or more of carbon black with 100 parts by mass of the aromatic polyether. 9. A method for producing the resin composition according to 8, wherein the amount of carbon black blended with 100 parts by mass of the aromatic polyether is 10 parts by mass or less. [Effects of the Invention]

[0009] According to the present invention, it is possible to provide a resin composition containing an aromatic polyether, a method for producing the resin composition, and a sheet that exhibits excellent thermal stability and excellent mechanical properties of molded articles. [Brief explanation of the drawing]

[0010] [Figure 1] This figure shows the 1H-NMR spectrum of PEEK(A) obtained in Production Example 1. [Modes for carrying out the invention]

[0011] The present invention's aromatic polyether and method for producing the aromatic polyether will be described in detail below. In this specification, "x~y" represents a numerical range of "greater than or equal to x and less than or equal to y". The upper and lower limits specified for the numerical range can be combined in any way. Furthermore, it is possible to combine two or more non-conflicting embodiments of the embodiments of the present invention described below, and an embodiment that combines two or more embodiments is also an embodiment of the embodiments of the present invention.

[0012] 1.Resin composition A resin composition according to one aspect of the present invention comprises a structural unit represented by the following formula (1), a structural unit represented by the following formula (2), and a structure represented by the following formula (3), 1The aromatic polyether comprises an aromatic polyether in which the ratio of the peak intensity of the peak originating from the structural unit represented by formula (2) that appears around a chemical shift of 7.34 ppm in 1H-NMR measurements to the peak intensity of the peak originating from the structure represented by formula (3) that appears in the chemical shift range of 7.69 ppm to 7.75 ppm (hereinafter sometimes simply referred to as "intensity ratio X") is greater than 0%, and carbon black in an amount of 0.01 parts by mass or more per 100 parts by mass of the aromatic polyether. [ka]

[0013] According to the resin composition of this embodiment, the thickening and degradation of aromatic polyethers with a strength ratio X greater than 0% during melting are suppressed, and an effect of excellent thermal stability is obtained. In other words, aromatic polyethers with a strength ratio X greater than 0% tend to be more susceptible to problems such as thickening and degradation due to oxidation reactions during molding processes, for example, under prolonged heating conditions, compared to aromatic polyethers with a strength ratio X of 0%. According to the resin composition of this embodiment, thickening and degradation during melting are suppressed for aromatic polyethers with a strength ratio X greater than 0%, which are prone to such problems, and excellent thermal stability can be obtained.

[0014] The reasons for such effects are not limited to the following, but are thought to be the following: Carbon black is a particle with a graphene structure and a molecular structure with high electron density. Therefore, by incorporating carbon black into a resin composition containing aromatic polyether, for example, when radical components are generated during heating and melting of the resin composition, the carbon black in the composition can capture (trap) the radical components. This makes it possible to suppress the occurrence of decomposition reactions of aromatic polyether caused by radical components and the resulting degradation. Furthermore, due to its structure, carbon black has the property of readily adhering to aromatic polyethers such as PEEK, which contain aromatic components at high density as structural units of the resin. Therefore, the effect of suppressing the decomposition reaction of aromatic polyethers, as described above, can be obtained even without incorporating a large amount of carbon black into the composition. Furthermore, because carbon black is a particle with a graphene structure, it has the property of easily penetrating between the resin chains of aromatic polyethers such as PEEK. By incorporating carbon black into a resin composition containing aromatic polyethers, the frequency of collisions between aromatic polyethers during heating and melting of the resin composition can be reduced, and reactions between aromatic polyethers and the resulting thickening can be suppressed with high efficiency.

[0015] As described above, suppressing the thickening of aromatic polyethers during melting improves the processability when manufacturing molded products by melting aromatic polyethers. Furthermore, suppressing the degradation of aromatic polyethers during melting improves the mechanical properties of molded products formed by melting aromatic polyethers. The mechanical properties referred to here may include, for example, tensile strength, tensile elongation, and toughness.

[0016] In one embodiment, the aromatic polyether according to this embodiment consists of one aromatic polyether having an equal strength ratio X.

[0017] In one embodiment, the aromatic polyether according to this embodiment is a mixture of two or more aromatic polyethers having different strength ratios X. In this case, the mixture 1 In 1H-NMR measurement, the intensity ratio X is greater than 0%. Here, the two or more aromatic polyethers may or may not include an aromatic polyether with an intensity ratio X of 0%.

[0018] In one embodiment, the intensity ratio X is 0.10% or more, 0.50% or more, or 1.0% or more, and 10.0% or less, 5.0% or less, or 3.0% or less. Furthermore, the intensity ratio X may be, for example, 0.10-5.0%, 0.50-2.0%, 0.80-1.7%, or 1.0-1.4%. This allows the effects of the present invention to be effectively demonstrated.

[0019] Furthermore, the intensity ratio X is as described in the examples. 1 These values ​​were obtained by 1H-NMR measurement.

[0020] In this embodiment, the aromatic polyether has one or more structural units represented by formula (3) located at the ends of the molecular chain. In one embodiment, the aromatic polyether has a structural unit represented by formula (1) located at one or more ends of the molecular chain. In this case, the terminal structure bonded to the structural unit may be a chlorine atom (Cl). In one embodiment, the aromatic polyether has a structural unit represented by formula (2) located at one or more ends of the molecular chain. In this case, the terminal structure bonded to the structural unit may be, for example, a hydrogen atom (H) (when the terminal structure is a hydrogen atom (H), a hydroxyl group is formed together with the oxygen atom (O) in the structural unit). In one embodiment, the terminal structure of the aromatic polyether may be, for example, a structure in which some of the chlorine atoms (Cl) or hydroxyl groups are replaced by hydrogen atoms (H), etc. However, the terminal structure is not limited to these examples and can be any structure.

[0021] In one embodiment, the aromatic polyether includes a structural unit represented by the following formula (4). [ka]

[0022] The structural unit represented by equation (4) is a combination of the structural unit represented by equation (1) and the structural unit represented by equation (2).

[0023] In one embodiment, the aromatic polyether does not contain any structures other than the structural units represented by formulas (1) to (3).

[0024] In one embodiment, the aromatic polyether includes structures other than the structural units represented by formulas (1) to (3), to the extent that the effects of the present invention are not impaired.

[0025] In one embodiment, the total percentage (mass%) of structural units represented by formula (1), formula (2), and formula (3) contained in the total monomer, based on the total monomer subjected to the reaction, is 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 97% by mass or more, 99% by mass or more, 99.5% by mass or more, or 100% by mass.

[0026] In one embodiment, in an aromatic polyether, the molar ratio of structural units represented by formula (1) to structural units represented by formula (2) (structural units represented by formula (1):structural units represented by formula (2)) is 47.5:52.5~52.5:47.5, 48.0:52.0~52.0:48.0, 48.5:51.5~51.5:48.5, 49.0:51.0~51.0:49.0, or 49.5:50.5~50.5:49.5. The number of moles of the structural unit represented by equation (1) may be greater than, less than, or the same as the number of moles of the structural unit represented by equation (2).

[0027] In one embodiment, the proportion (mass%) of the aromatic polyether obtained by reacting 4,4'-dichlorobenzophenone with hydroquinone, based on the total amount of the aromatic polyether, is 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 99% by mass or more, or 100% by mass.

[0028] In one embodiment, the melt flow index (abbreviated as "MI": synonymous with the melt flow rate (abbreviated as "MFR") described in ASTM D 1238-13) of the aromatic polyether is 1500 g / 10 min or less, 1000 g / 10 min or less, 500 g / 10 min or less, 300 g / 10 min or less, 200 g / 10 min or less, 100 g / 10 min or less, 80 g / 10 min or less, or 60 g / 10 min or less, and is also 0.0001 g / 10 min or more, 0.0005 g / 10 min or more, or 0.001 g / 10 min or more. In one embodiment, the melt flow index of the aromatic polyether is, for example, 0.0001 to 1500 g / 10 min, preferably 0.0005 to 500 g / 10 min, and more preferably 0.001 to 100 g / 10 min.

[0029] In one embodiment, the melt flow index of the aromatic polyether is preferably 100 g / 10 min or less. The aromatic polyether having a melt flow index of 100 g / 10 min or less has a sufficiently high molecular weight and can be preferably processed by pelletizing, for example, by an extruder. The melt flow index of aromatic polyethers can be adjusted by the temperature conditions of the reaction mixture (maximum temperature, temperature holding time, heating rate, etc.) and the ratio of raw materials (monomers, etc.) in the reaction mixture.

[0030] In one embodiment, the melt flow index of the aromatic polyether is a value measured by the following method. Measurements will be taken using a melt indexer (L-220) manufactured by Tateyama Science High Technologies Co., Ltd., in accordance with JIS K 7210-1:2014 (ISO 1133-1:2011), under the following measurement conditions. [Measurement conditions] ·Measurement temperature (resin temperature): 380℃ • Measured load: 2.16 kg • Cylinder bore diameter: 9.550 mm • Die inner diameter: 2.095 mm Die length: 8,000 mm • Piston head length: 6.35mm • Piston head diameter: 9.474 mm • Piston weight: 110.0g (The above measured load includes the piston weight) ·operation: The sample is dried beforehand at 150°C for at least 2 hours. The sample is placed in the cylinder, the piston is inserted, and preheating is performed for 6 minutes. A load is applied, the piston guide is removed, and the molten sample is pushed out of the die. The sample is cut within a predetermined range of piston movement and for a predetermined time (t[s]), and its weight is measured (m[g]). The MI is calculated using the following formula: MI[g / 10min] = 600 / t × m

[0031] The resin composition according to this embodiment contains 0.01 parts by mass or more of carbon black per 100 parts by mass of aromatic polyether. Carbon black refers to fine black carbon powder obtained by thermal decomposition or incomplete combustion of hydrocarbons such as oil and natural gas. Examples of carbon black include furnace black produced by the furnace process, acetylene black produced by the acetylene process, thermal black produced by the thermal process, channel black produced by the channel process, and Ketjen black.

[0032] In one embodiment, the carbon black content in the resin composition is 0.02 parts by mass or more, 0.03 parts by mass or more, or 0.04 parts by mass or more per 100 parts by mass of aromatic polyether. By ensuring that the carbon black content is above the lower limit, the thickening and degradation of the aromatic polyether during melting can be effectively suppressed. The upper limit of the carbon black content is not particularly limited, but from the viewpoint of obtaining excellent mechanical strength in a molded article obtained with the resin composition according to this embodiment, for example, it is 10 parts by mass or less, 8 parts by mass or less, 5 parts by mass or less, 1 part by mass or less, 0.7 parts by mass or less, or 0.5 parts by mass or less per 100 parts by mass of aromatic polyether.

[0033] In one embodiment, the dibutyl phthalate (DBP) absorption of carbon black is 40 cm 3 / 100 g or more, 50 cm 3 / 100 g or more, 60 cm 3 / 100 g or more, 70 cm 3 / 100 g or more, 75 cm 3 / 100 g or more, 80 cm 3 / 100 g or more, or 85 cm 3 / 100 g or more, and also 400 cm 3 / 100 g or less, 350 cm 3 / 100 g or less, or 300 cm 3 ) / 100 g or less. The DBP absorption is a value measured in accordance with JIS K6217-4 and is an index of the degree of development (structure) of the state where the primary particles of carbon black are fused together. When the DBP absorption of carbon black is at least the lower limit value, thickening and deterioration of the aromatic polyether during melting can be favorably suppressed. Also, when the DBP absorption of carbon black is at most the upper limit value, aggregation of carbon black in the composition can be suppressed.

[0034] In one embodiment, the pH of carbon black is 4.0 or more, 5.0 or more, 6.0 or more, or 7.0 or more. The pH of carbon black is shown as an index of the number of functional groups (for example, phenolic hydroxyl groups, carboxyl groups, etc.) on the surface of carbon black. When it is at least the lower limit value, thickening and deterioration of the aromatic polyether during melting can be favorably suppressed. In one embodiment, the pH of carbon black is preferably 4.0 or more, and particularly preferably 7.0 or more. In one embodiment, the upper limit of the pH of carbon black is not particularly limited, but from the viewpoint of suppressing aggregation of carbon black, it is, for example, 14.0 or less, or 12.0 or less. Incidentally, the pH of carbon black can be measured by a method in accordance with ASTM D1512.

[0035] In one embodiment, the average particle size of the carbon black is 5 nm or more, 7 nm or more, 10 nm or more, or 15 nm or more, and also 200 nm or less, 150 nm or less, or 100 nm or less. In one embodiment, the average particle size of the carbon black may be 5-200 nm, 10-100 nm, or 17-75 nm. By keeping the average particle size above the lower limit, the thickening and degradation of the aromatic polyether during melting can be effectively suppressed. Furthermore, by keeping the average particle size below the upper limit, excellent mechanical strength can be obtained in molded articles made from the resin composition.

[0036] Furthermore, the average particle size of carbon black can be measured by the following method. The carbon black recovered from the resin composition is observed using an electron microscope, and the average particle size is calculated by calculating the arithmetic mean of a predetermined number (e.g., 50) of carbon black particles confirmed in the electron microscope image.

[0037] In one embodiment, the specific surface area of ​​carbon black is 10 m². 2 / g or more, 20m 2 / g or more, 25m 2 / g or more, 29m 2 / g or more, or 30m 2 It is 1 / g or more, and also 250m 2 / g or less, 240m 2 / g or less, 230m 2 / g or less, 200m 2 / g or less, 100m 2 / g or less, or 85m 2 It is less than / g. By keeping the specific surface area below the upper limit, the thickening and degradation of the aromatic polyether during melting can be effectively suppressed. Furthermore, by keeping the specific surface area above the lower limit, excellent mechanical strength can be obtained in molded articles made from the resin composition.

[0038] Furthermore, the specific surface area of ​​carbon black can be measured in accordance with JIS K6217-2.

[0039] In one embodiment, the resin composition has an MFR of 4 [g / 10min] measured after preheating the resin composition at 380°C for 4 minutes, and an MFR of 4 [g / 10min] measured after preheating the resin composition at 380°C for 60 minutes. 60 [g / 10min] Ratio (MFR4 / MFR 60 The ratio (MFR4 / MFR) may be 1.12 or less, 1.11 or less, 1.10 or less, 1.09 or less, 1.08 or less, 1.07 or less, 1.06 or less, or 1.05 or less. 60 The lower limit of ) is not particularly limited; for example, it is 0.98 or higher. This ratio (MFR4 / MFR 60 The smaller the value, the more suppressed the thickening of the aromatic polyether during melting. Furthermore, MFR4 and MFR 60 This is a value measured by the method described in the examples.

[0040] MFR4 and MFR of resin composition 60 The individual values ​​are not particularly limited. In one embodiment, MFR4 is 1-30 g / 10 min, 3-28.5 g / 10 min, or 5-26 g / 10 min. In one embodiment, MFR 60 The recommended daily intake is 1-30g / 10min, 3-28.5g / 10min, or 5-26g / 10min.

[0041] In one embodiment, the resin composition may contain various additives, such as known antioxidants, in addition to the aromatic polyether and carbon black described above.

[0042] In one embodiment, 70% or more by mass of the resin composition, 80% or more by mass, 90% or more by mass, 95% or more by mass, 99% or more by mass, 99.5% or more by mass, 99.9% or more by mass, or substantially 100% by mass is These are aromatic polyethers and carbon blacks with a strength ratio X greater than 0%. Furthermore, in the case of "substantially 100% by mass," it is acceptable for unavoidable impurities to be present.

[0043] Using the resin composition according to this embodiment, for example, pellets containing the resin composition can be manufactured. These pellets can be used as various molding materials requiring heat resistance, solvent resistance, insulation, etc. Using these pellets, molded articles can be manufactured by molding methods such as injection molding using a mold. Furthermore, using these pellets, molded articles can be manufactured by molding methods such as extrusion molding, press molding, sheet molding, and film molding. The applications of the resin composition according to this embodiment are not particularly limited. The resin composition according to this embodiment is suitable, for example, for aerospace applications, sliding components such as gears and bearings, and various other resin compositions. Molded articles containing the resin composition according to this embodiment are suitable, for example, as aerospace molded articles, molded articles for sliding members, and filaments for 3D printers. Furthermore, molded articles containing the resin composition are suitable, for example, as injection molded articles for aerospace and injection molded articles for sliding members.

[0044] In one embodiment, the tensile strength of a molded article obtained using a resin composition according to one aspect of the present invention is 70 MPa or more, 80 MPa or more, 90 MPa or more, or 95 MPa or more. The upper limit of the tensile strength is not particularly limited, but for example, it may be 500 MPa or less, 200 MPa or less, 150 MPa or less, or 120 MPa or less. The tensile strength of the molded article is the value obtained by the tensile strength measurement method described in the examples.

[0045] In one embodiment, the tensile elongation of a molded article obtained using a resin composition according to one aspect of the present invention is 1% or more, 3% or more, 6% or more, or 7% or more. The upper limit of the tensile elongation is not particularly limited, but for example, it may be 100% or less, 70% or less, 60% or less, 55% or less, 50% or less, or 20% or less. The tensile elongation of the molded article is the value obtained by the tensile elongation measurement method described in the examples.

[0046] In one embodiment, the number of ductile fractures in a molded article obtained with a resin composition according to one aspect of the present invention is 1 or more, 2 or more, 3 or more, 4 or more, or 5 or more. The number of ductile fractures in the molded article is the value obtained by the ductile fracture measurement method described in the examples.

[0047] The method for producing the resin composition according to one aspect of the present invention described above is not particularly limited, but for example, it can be produced by the method for producing the resin composition according to one aspect of the present invention described below.

[0048] 2. Method for producing resin compositions A method for producing a resin composition according to one aspect of the present invention is a method for producing the resin composition according to one aspect of the present invention described above, comprising the steps of: reacting a mixture containing 4,4'-dichlorobenzophenone and hydroquinone to produce an aromatic polyether (step (a)); and mixing 0.01 parts by mass or more of carbon black with 100 parts by mass of the aromatic polyether (step (b)).

[0049] (Step (a)) First, an aromatic polyether is produced by reacting a mixture containing 4,4'-dichlorobenzophenone and hydroquinone. 4,4'-Dichlorobenzophenone and hydroquinone are monomers of aromatic polyethers. By including 4,4'-Dichlorobenzophenone as a monomer, the intensity ratio X in the resulting aromatic polyether can be increased to greater than 0%. Furthermore, by using 4,4'-Dichlorobenzophenone and hydroquinone as raw materials during the synthesis of aromatic polyethers, and increasing the ratio of 4,4'-Dichlorobenzophenone to hydroquinone used, the intensity ratio X in the aromatic polyether can be increased to greater than 0%. Aromatic polyethers can be obtained as copolymers of these compounds (monomer units) through a process of reacting 4,4'-dichlorobenzophenone and hydroquinone. 4,4'-Dichlorobenzophenone and hydroquinone are available commercially.

[0050] In the following description, "reaction mixture" refers to the reaction system from the start to the completion of the reaction between 4,4'-dichlorobenzophenone and hydroquinone, and is preferably in the form of a solution containing these monomers in addition to the solvent described later. The composition of the reaction mixture may change as the reaction progresses. Typically, as the reaction proceeds, the concentrations of the reactants (4,4'-dichlorobenzophenone and hydroquinone) in the reaction mixture decrease, while the concentration of the product (aromatic polyether) increases.

[0051] Furthermore, the "maximum temperature" of the reaction mixture refers to the highest temperature reached by the reaction mixture (maximum temperature attained) during the process from the start of the reaction between 4,4'-dichlorobenzophenone and hydroquinone to the completion of the reaction. The maximum temperature of the reaction mixture is not particularly limited, but is, for example, 260 to 360°C, preferably more than 290°C and 360°C or less, more preferably 295 to 360°C, and even more preferably 295 to 340°C.

[0052] In one embodiment, the process for producing an aromatic polyether includes holding the reaction mixture at 180-220°C for 0.5-2 hours, preferably 0.6-1.8 hours, and more preferably 0.7-1.5 hours (hereinafter also referred to as "temperature holding (i)"). This allows the reaction to be promoted while suppressing the volatilization of the raw materials, and a higher molecular weight aromatic polyether can be obtained.

[0053] In one embodiment, the process for producing an aromatic polyether includes holding the reaction mixture at 230-270°C for 0.5-2 hours, preferably 0.6-1.8 hours, and more preferably 0.7-1.5 hours (hereinafter also referred to as "temperature holding (ii)"). This allows the reaction to be promoted while suppressing the volatilization of the raw materials, and a higher molecular weight aromatic polyether can be obtained.

[0054] In one embodiment, the process for producing an aromatic polyether includes holding the reaction mixture at 280 to 360°C for 0.5 to 8 hours, preferably 0.7 hours or more, 1 hour or more, 2 hours or more, 3 hours or more, 4 hours or more, 5 hours or more, 8 hours or less, 6 hours or less, for example, 0.5 hours or more and 3 hours or less (the upper and lower limits can be any combination) (hereinafter also referred to as "temperature holding (iii)"). This makes it possible to obtain an aromatic polyether with a desired molecular weight.

[0055] In one embodiment, the process for producing an aromatic polyether may include two or three steps selected from the group consisting of the above temperature holding steps (i) to (iii). The two or three temperature holding steps are preferably carried out in order from the lowest temperature. The reaction mixture may be heated between the two or three temperature holding steps.

[0056] The heating rate when raising the temperature of the reaction mixture is not particularly limited and can be, for example, 0.1-15°C / min, 0.1-10°C / min, 0.1-8°C / min, or 0.1-5°C / min. This allows the reaction to be promoted while suppressing the volatilization of the raw materials, and a higher molecular weight aromatic polyether can be obtained.

[0057] In one embodiment, the process for producing an aromatic polyether involves a time interval of 2.0 to 10 hours from the point when the temperature of the reaction mixture reaches 150°C until it reaches its maximum temperature.

[0058] In one embodiment, the reaction mixture includes a solvent. The reaction mixture containing the solvent may be in the form of a solution. The solution may include 4,4'-dihalogenobenzophenone, hydroquinone, and diphenylsulfone having one reactive group, all dissolved in the solvent. The solvent is not particularly limited, and for example, a neutral polar solvent can be used. Examples of neutral polar solvents include N,N-dimethylformamide, N,N-diethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N,N-dipropylacetamide, N,N-dimethylbenzoic acid amide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-isopropyl-2-pyrrolidone, N-isobutyl-2-pyrrolidone, Nn-propyl-2-pyrrolidone, Nn-butyl-2-pyrrolidone, N-cyclohexyl-2-pyrrolidone, N-methyl-3-methyl-2-pyrrolidone, Examples include N-ethyl-3-methyl-2-pyrrolidone, N-methyl-3,4,5-trimethyl-2-pyrrolidone, N-methyl-2-piperidone, N-ethyl-2-piperidone, N-isopropyl-2-piperidone, N-methyl-6-methyl-2-piperidone, N-methyl-3-ethylpiperidone, dimethyl sulfoxide, diethyl sulfoxide, 1-methyl-1-oxosulfolane, 1-ethyl-1-oxosulfolane, 1-phenyl-1-oxosulfolane, N,N'-dimethylimidazolidinone, and diphenyl sulfone. Among these, diphenyl sulfone is particularly preferred.

[0059] In one embodiment, the reaction mixture contains an aromatic sulfone such as diphenyl sulfone, and the content of a solvent with a boiling point of 270-330°C is 0 parts by mass or more and less than 1 part by mass per 100 parts by mass of the aromatic sulfone. This makes it easy to control the reaction temperature.

[0060] The reaction mixture may contain one or more solvents. In particular, it is preferable that the reaction mixture contains only one solvent (single solvent), which simplifies the process.

[0061] In one embodiment, the reaction mixture contains a base. The presence of the base in the reaction mixture promotes the reaction. The base is not particularly limited, but alkali metal salts are preferred, for example. The alkali metal salt is not particularly limited, and examples include alkali metal carbonates, alkali metal bicarbonates, alkali metal hydrides, alkali metal hydroxides, etc. Examples of alkali metal carbonates include potassium carbonate, sodium carbonate, lithium carbonate, rubidium carbonate, and cesium carbonate. Examples of alkali metal bicarbonates include lithium bicarbonate, sodium bicarbonate, potassium bicarbonate, rubidium bicarbonate, and cesium bicarbonate. Among these, potassium carbonate is particularly preferred. These bases may be used individually or in combination of two or more.

[0062] In one embodiment, the reaction mixture contains potassium carbonate. In one embodiment, the reaction mixture contains bases other than potassium carbonate. These bases may be used in combination with potassium carbonate. For example, potassium carbonate and sodium carbonate may be used in combination.

[0063] The total concentration of bases in the reaction mixture is not particularly limited. In one embodiment, the total amount of base in the reaction mixture is 100 mol parts or more, and also 180 mol parts or less, 160 mol parts or less, 140 mol parts or less, or 120 mol parts or less, per 100 mol parts of hydroquinone added to the reaction mixture. If the total amount of base is 100 mol parts or more, the reaction time can be shortened. If the total amount of base is 180 mol parts or less, the formation of gel components can be suppressed. Furthermore, the total amount of base in the reaction mixture is, for example, 100 to 180 mol parts, preferably 100 to 140 mol parts, and more preferably 100 to 120 mol parts, per 100 mol parts of hydroquinone added to the reaction mixture. In one embodiment, potassium carbonate is added as a base in the above-mentioned proportion.

[0064] The molar ratio ([DCBP]:[HQ]) of 4,4'-dichlorobenzophenone (DCBP) to hydroquinone (HQ) used in the reaction is not particularly limited. The molar ratio ([DCBP]:[HQ]) can be adjusted as appropriate for purposes such as controlling the molecular weight of the resulting aromatic polyether. In one embodiment, the molar ratio ([DCBP]:[HQ]) is 0.970 to 1.100:1, 1.000 to 1.060:1, 1.000 to 1.040:1, or 1.010 to 1.040:1.

[0065] In one embodiment, the total concentration (based on the amount of each compound) of 4,4'-dichlorobenzophenone and hydroquinone in the reaction mixture is not particularly limited, and may be, for example, 1.0 mol / l or more, 1.2 mol / l or more, 1.3 mol / l or more, 1.4 mol / l or more, or 1.5 mol / l or more, or 6.0 mol / l or less, 5.0 mol / l or less, or 4.0 mol / l or less. Furthermore, the total concentration (based on the amount of each compound) of 4,4'-dichlorobenzophenone and hydroquinone in the reaction mixture may be, for example, 1.0 to 6.0 mol / l, preferably 1.3 to 5.0 mol / l, and more preferably 1.5 to 4.0 mol / l.

[0066] In one embodiment, no monomers other than 4,4'-dichlorobenzophenone and hydroquinone are used as monomers in the reaction described above.

[0067] In one embodiment, other monomers other than 4,4'-dichlorobenzophenone and hydroquinone may be used in combination with the above-described reaction, to the extent that they do not impair the effects of the present invention.

[0068] In one embodiment, the total percentage (mass%) of 4,4'-dichlorobenzophenone and hydroquinone, based on the total monomers subjected to the reaction, is 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 97% by mass or more, 99% by mass or more, 99.5% by mass or more, or 100% by mass.

[0069] In one embodiment, the above-described reaction may be combined with other dihalogenated monomers other than 4,4'-dichlorobenzophenone, to the extent that the effects of the present invention are not impaired.

[0070] In one embodiment, the proportion (mass%) of 4,4'-dichlorobenzophenone, based on the dihalogenated monomer subjected to the reaction, is 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 97% by mass or more, 99% by mass or more, 99.5% by mass or more, or 100% by mass.

[0071] In one embodiment, at the start of the reaction, 70% or more by mass of the reaction mixture, 80% or more by mass, 90% or more by mass, 95% or more by mass, 99% or more by mass, 99.5% or more by mass, 99.9% or more by mass, or substantially 100% by mass is 4,4'-Dichlorobenzophenone, hydroquinone, alkali metal salt, and solvent, One or more alkali metal salts selected from the group consisting of 4,4'-dichlorobenzophenone, hydroquinone, potassium carbonate, and sodium carbonate, and diphenyl sulfone, or These are 4,4'-dichlorobenzophenone, hydroquinone, potassium carbonate, and diphenyl sulfone. Furthermore, in the case of "substantially 100% by mass," it is acceptable for unavoidable impurities to be present.

[0072] The reaction between 4,4'-dichlorobenzophenone and hydroquinone can be carried out in an inert gas atmosphere. The inert gas is not particularly limited and examples include nitrogen and argon.

[0073] (Step (b)) Next, 0.01 parts by mass or more of carbon black is mixed with 100 parts by mass of the aromatic polyether obtained in step (a).

[0074] In one embodiment, the mixing ratio of carbon black is 0.02 parts by mass or more, 0.03 parts by mass or more, or 0.04 parts by mass or more per 100 parts by mass of aromatic polyether, and is also 10 parts by mass or less, 8 parts by mass or less, 5 parts by mass or less, 1 part by mass or less, or 0.7 parts by mass or less.

[0075] With regard to the types of carbon black to be mixed with aromatic polyethers and the preferred range of their properties (DBP absorption, pH, average particle size, specific surface area), the description of carbon black contained in a resin composition according to one embodiment of the present invention should be referenced.

[0076] The method for mixing aromatic polyether and carbon black is not particularly limited, and known methods can be used. For example, aromatic polyether and carbon black can be mixed at room temperature, and then mixed by a method such as melt kneading; the method is not particularly limited. As a mixing method, melt kneading using a twin-screw extruder is preferably used.

[0077] Furthermore, the state of the aromatic polyether and carbon black before melting and kneading is not particularly limited. For example, the carbon black may be in powder form, or it may be mixed with a known solvent to form pellets. The aromatic polyether may also be molded into pellets.

[0078] In melt kneading using a twin-screw extruder, it is preferable to knead with an appropriate temperature gradient, for example, in a temperature range of 100 to 450°C, preferably 180 to 400°C. When melt-kneading with a temperature gradient, the temperature immediately after adding the raw materials may be set to, for example, 100 to 300°C, preferably 180 to 400°C, and the melt-kneading may be carried out while gradually or stepwise raising the temperature to a higher temperature than immediately after adding the raw materials, for example, in the range of 300 to 450°C. In melt kneading using a twin-screw extruder, the screw rotation speed of the twin-screw extruder is not particularly limited, but can be set to, for example, 150 to 300 rpm, preferably 200 to 280 rpm.

[0079] Furthermore, the equipment used for melting and kneading is not limited to twin-screw extruders; other known equipment such as single-screw extruders and injection molding machines can be used. [Examples]

[0080] The following describes embodiments of the present invention, but the present invention is not limited to these embodiments.

[0081] (Manufacturing Example 1) A 2000 ml four-necked flask equipped with a stirrer, thermometer, nitrogen inlet tube, and water recovery container connected to a condenser contained 144.92 g (0.5771 mol) of 4,4'-dichlorobenzophenone, 61.69 g (0.5603 mol) of hydroquinone, 89.05 g (0.6443 mol) of potassium carbonate, and 485.11 g of diphenyl sulfone, and nitrogen gas was circulated through it.

[0082] The reaction mixture was carried out under the following temperature control. <Temperature control> (1) After raising the temperature to 150°C, raise the temperature to 200°C over a period of 30 minutes. (2) Hold at 200°C for 1 hour (3) Increase the temperature from 200°C to 250°C (heating rate 0.7°C / min) (4) Hold at 250°C for 1 hour (5) Increase the temperature from 250°C to 300°C (the maximum temperature of the reaction mixture) (heating rate 0.45°C / min) (6) Hold at 300°C (the highest temperature of the reaction mixture) for 5 hours.

[0083] After the reaction was complete, the product was pulverized in a blender (Waring 7010HS), washed with acetone and then water, and then dried in a dryer at 180°C to obtain powdered aromatic polyether (PEEK(A)).

[0084] (Manufacturing example 2) Aromatic polyether (PEEK(B)) was obtained in the same manner as in Production Example 1, except that the amount of 4,4'-dichlorobenzophenone was changed to 144.21 g (0.5743 mol).

[0085] ( 1 H-NMR measurement (intensity ratio X)) Aromatic polyethers 1 The samples were subjected to 1H-NMR measurement, and the ratio (intensity ratio X) of the peak intensity (I2) of the peak originating from the structure represented by equation (2) that appears around chemical shift 7.34 ppm to the peak intensity (I3) of the peak originating from the structure represented by equation (3) that appears in the range of chemical shift 7.69 ppm to 7.75 ppm was determined using the following formula. Intensity ratio X[%]=(I3 / I2)×100 Furthermore, the "peak originating from the structure represented by equation (2) appearing around chemical shift 7.34 ppm" specifically originates from the four hydrogen atoms on the benzene ring in the structure represented by equation (2). This peak may appear around chemical shift 7.34 ppm, for example, in the range of chemical shift 7.32 to 7.40. 1 In 1H-NMR measurements, the structural unit represented by formula (3) has two bonds attached to the 2nd and 6th positions of the terminal phenyl group in the structural unit represented by formula (3), respectively. 1 This is observed as a peak in H. Furthermore, the presence of the structure represented by formula (3) in the aromatic polyether indicates that 1 This can be confirmed by combining and analyzing methods such as H-NMR measurement, 2D NMR measurement, and mass spectrometry.

[0086] As mentioned above 1 The measurement conditions for H-NMR are as follows. < 1 Measurement conditions for H-NMR measurement > • NMR spectrometer: Bruker Japan Co., Ltd. "Ascend500" • Probe: 5mm diameter TCI cryopreole ·NMR sample tube diameter: 5mm in diameter • Sample solution preparation: Approximately 20 mg of the sample was mixed with 0.6 ml of methanesulfonic acid and stirred at room temperature for 1 hour. Then, 0.4 ml of deuterated dichloromethane was added and stirred at room temperature for another 30 minutes to dissolve the sample and prepare the sample solution. • Observation range: 20 ppm • Observation center: 6.175 ppm • Number of data points: 64kB • Pulse repetition time: 10 seconds • Total number of times: 256 • Flip angle: 30° ·Measurement temperature: 25℃ • Chemical shift reference: The middle of the three heavy dichloromethane peaks is set to 5.32 ppm.

[0087] Figure 1 shows the PEEK(A) obtained in manufacturing example 1. 1 The H-NMR spectrum is shown. In Figure 1, peak 2 represents the peak derived from the structure represented by equation (2), and peak 3 represents the peak derived from the structure represented by equation (3). The dashed box in Figure 1 represents the range of chemical shifts from 7.65 ppm to 7.75 ppm. 1 The H-NMR spectrum is shown in magnified view.

[0088] The carbon blacks CB1 to CB4 used in the following examples and comparative examples are shown below. Carbon Black CB1: Manufactured by Mitsubishi Chemical Corporation, "RCF #10", average particle size: 75 [nm], pH = 8.4, specific surface area: 30 [m²] 2 / g], DBP absorption: 86 [cm³ 3 / 100g] Carbon Black CB2: Manufactured by Mitsubishi Chemical Corporation, "RCF #20", average particle size: 50 [nm], pH = 9.6, specific surface area: 45 [m²] 2 / g], DBP absorption: 122 [cm³ 3 / 100g] Carbon Black CB3: Manufactured by Mitsubishi Chemical Corporation, "RCF #32", average particle size: 30 [nm], pH = 8.3, specific surface area: 83 [m²] 2 / g], DBP absorption: 98 [cm³ 3 / 100g] Carbon Black CB4: Manufactured by Mitsubishi Chemical Corporation, "MCF #850", average particle size: 17 [nm], pH = 7.0, specific surface area: 220 [m²] 2 / g], DBP absorption: 78 [cm³ 3 / 100g]

[0089] (Example 1) To 100 parts by mass of aromatic polyether (PEEK(A)) obtained in Production Example 1, 0.05 parts by mass of carbon black CB1 was mixed, and the mixture was kneaded using a twin-screw extruder (Thermo Fisher Scientific Co., Ltd., "Process-11") at a kneading temperature (barrel 1: 200°C, barrels 2-7 & die head (DH): 370°C), a screw rotation speed of 250 rpm, and a discharge rate of 0.4 kg / hr to obtain a resin composition.

[0090] The obtained resin composition was subjected to the following measurements (1) and (2).

[0091] (1) Thickening ratio MFR4 / MFR 60 Measurement For the resin composition, the MFR was measured using a melt indexer (L-220) manufactured by Tateyama Science High Technologies Co., Ltd., in accordance with JIS K 7210-1:2014 (ISO 1133-1:2011), under the following measurement conditions. [Measurement conditions] ·Measurement temperature (resin temperature): 380℃ • Measured load: 2.16 kg • Cylinder bore diameter: 9.550 mm • Die inner diameter: 2.095 mm Die length: 8,000 mm • Piston head length: 6.35mm • Piston head diameter: 9.474 mm • Piston weight: 110.0g (The above measured load includes the piston weight) ·operation: The sample was pre-dried at 150°C for at least 2 hours. The sample was placed in a cylinder, the piston was inserted, and the sample was preheated in the cylinder for a predetermined time. Then, A load was applied, the piston guide was removed, and the molten sample was pushed out of the die. The sample was cut within a predetermined range of piston movement and for a predetermined time (t [s]), and its mass was measured (m [g]). The mass-free flow rate (MFR) was calculated using the following formula: MFR [g / 10min] = 600 / t × m The MFR measured when the preheating time (corresponding to the melting time) is 4 minutes is defined as MFR4 [g / 10min], and the MFR measured when the preheating time is 60 minutes is defined as MFR 60 [g / 10min] is used as the ratio of these values ​​(MFR4 / MFR 60 The viscosity was calculated and used as the thickening rate.

[0092] (2) Tensile strength, tensile elongation, and number of ductile fractures The resin composition was dried at 180°C for more than 2 hours, and then injection molded using a Thermo Fisher Scientific MinijetPro (cylinder temperature 380°C, mold temperature 180°C, injection pressure 500 bar, holding pressure 500 bar, holding time 15 seconds) to obtain ISO 5A type dumbbell (2 mm thick) test specimens. Tensile tests were performed on the obtained test specimens at a test speed of 20 mm / min and a chuck distance of 50 mm, and the tensile strength and tensile elongation (strain) were measured. Furthermore, in the tensile tests described above, fracture patterns showing an elongation of 1% or more after the yield point appeared were defined as ductile fracture, and all other fracture patterns were defined as brittle fracture. The number of ductile fractures was then evaluated.

[0093] The results are shown in Table 1.

[0094] (Examples 2-8) The aromatic polyethers (PEEK(A), PEEK(B)) and carbon blacks CB1 to CB4 obtained in Production Examples 1 and 2 were mixed in the amounts shown in Table 1 to obtain the resin compositions of Examples 2 to 8.

[0095] The carbon black content shown in Table 1 is expressed as the ratio (parts by mass) of carbon black to 100 parts by mass of aromatic polyether (PEEK(A) or PEEK(B)).

[0096] The resin compositions of Examples 2 to 8 were subjected to the same measurements as in Example 1. The results are shown in Table 1.

[0097] (Comparative Example 1) The resin composition of Comparative Example 1 was obtained in the same manner as in Example 1, except that carbon black was not added to the aromatic polyether (PEEK(A)) obtained in Production Example 1. The resin composition of Comparative Example 1 was subjected to the same measurements as in Example 1. The results are shown in Table 1.

[0098] (Comparative Example 2) A resin composition for Comparative Example 2 was obtained in the same manner as in Example 8, except that trisodium phosphate (anhydrous) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (0.5 parts by mass) was added as an additive instead of carbon black CB4 (0.5 parts by mass). The resin composition of Comparative Example 2 was subjected to the same measurements as in Example 1. The results are shown in Table 1.

[0099] [Table 1]

[0100] Table 1 shows that the resin compositions of Examples 1-8 have a higher viscosity (MFR4 / MFR) compared to the resin compositions of Comparative Examples 1 and 2. 60 It can be seen that the value is small and the thermal stability is high. Furthermore, it can be seen that the molded articles obtained from the resin compositions of Examples 1 to 8 have greater tensile strength and tensile elongation, and superior mechanical strength compared to the molded article obtained from the resin composition of Comparative Example 1.

Claims

1. The polymerizable compound includes a structural unit represented by the following formula (1), a structural unit represented by the following formula (2), and a structure represented by the following formula (3), 1 an aromatic polyether in which the ratio of the peak intensity of the peak having the greatest peak intensity among the peaks derived from the structure represented by formula (3) appearing in a chemical shift range of 7.69 ppm to 7.75 ppm to the peak intensity of the peak derived from the structural unit represented by formula (2) appearing in a chemical shift of about 7.34 ppm in H-NMR measurement is greater than 0%; A resin composition comprising 0.01 parts by mass or more of carbon black per 100 parts by mass of the aromatic polyether. 【Chemistry 5】

2. The resin composition according to claim 1 , wherein the content of the carbon black is 10 parts by mass or less based on 100 parts by mass of the aromatic polyether.

3. The carbon black has a dibutyl phthalate absorption of 40 to 400 cm 3 The resin composition according to claim 1 or 2, wherein the composition is a weight average molecular weight of 100 g / 100 g.

4. The resin composition according to claim 1 or 2, wherein the carbon black has a pH of 4.0 or more.

5. The resin composition according to claim 1 or 2, wherein the carbon black has an average particle size of 5 to 200 nm.

6. The specific surface area of ​​the carbon black is 10 to 250 m 2 The resin composition according to claim 1 or 2, wherein the molecular weight is 1000 or more.

7. The resin composition according to claim 1 or 2, wherein the aromatic polyether comprises a structural unit represented by the following formula (4): 【Chemistry 6】

8. reacting 4,4'-dichlorobenzophenone with hydroquinone to produce an aromatic polyether; The method for producing a resin composition according to claim 1 or 2, further comprising the step of mixing 0.01 part by mass or more of carbon black with respect to 100 parts by mass of the aromatic polyether.

9. The method for producing a resin composition according to claim 8, wherein the blending amount of the carbon black is 10 parts by mass or less based on 100 parts by mass of the aromatic polyether.